Changes in T Lymphocyte Subsets in Different Tumors Before and After Radiotherapy: A Meta-analysis - Wang, Qin; Li, Shangbiao; Qiao, Simiao; Zheng, Zhihao; Duan, Xiaotong; Zhu, Xiaoxia (Frontiers in Immunology, 2021)
Purpose: Radiation therapy (RT) induces an immune response, but the relationship of this response with tumor type is not fully understood. This meta-analysis further elucidated this relationship by analyzing the changes in T lymphocyte subsets in different tumors before and after radiotherapy. Methods: We searched English-language electronic databases including PubMed, EMBASE, and the Cochrane Library to collect studies on the changes in peripheral blood CD3+ T lymphocytes, CD4+ T lymphocytes, and CD8+ T lymphocytes before and after radiotherapy in tumor patients from January 2015 to April 2021. The quality of the included literature was evaluated using the NOS scale provided by the Cochrane Collaboration, and statistical software RevMan 5.4 was used to analyze the included literature. P<0.05 was considered to indicate statistical significance. Results: A total of 19 studies in 16 articles involving 877 tumor patients were included. All data were collected within 1 month before or after radiotherapy. Meta-analysis showed that numbers of CD3+ T lymphocytes (SMD: -0.40; 95% CI [-0.75, -0.04]; p=0.03) and CD4+T lymphocytes (SMD: -0.43; 95% CI: [-0.85, -0.02]; p=0.04) were significantly reduced after radiotherapy compared with before treatment, but there was no statistically significant difference for CD8+ T lymphocytes (SMD: 0.33; 95% CI: [ -0.88, 0.74]; p=0.12).Subgroup analysis showed that peripheral blood T lymphocytes decreased in head and neck cancer. However, in prostate cancer and breast cancer, there was no significant change in peripheral blood.1 month after radiotherapy, it has a potential proliferation and activation effect on lymphocytes in esophageal cancer and lung cancer. The results showed that CD8+T lymphocytes increased in peripheral blood after SBRT.Radiotherapy alone reduced CD3+ T lymphocyte numbers. Conclusions: Within 1 month of radiotherapy, patients have obvious immunological changes, which can cause apoptosis and reduction of T lymphocytes, and affect the balance of peripheral blood immune cells. The degree of immune response induced by radiotherapy differed between tumor types.